Sekolah Rasa Pesantren: Implementasi Kurikulum Integratif di Aya Sophia Islamic School - Masduki Asbari; Wakhida Nurhayati; Danish Akbar Firdausy Asbari; Raihan Arsyad Firdausy Asbari (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This article discusses the implementation of integrative curriculum management at Aya Sophia Islamic School, which combines the National Education Curriculum and the Madrasah Diniyah Curriculum. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and literature study. The results showed that this curriculum integration creates a holistic learning environment, where students not only achieve good academic performance but also experience character and moral strengthening through in-depth religious teaching. Parents report high satisfaction with their children's academic and attitudinal progress, making Aya Sophia Islamic School an attractive option for parents seeking quality education. The theoretical, practical and managerial implications of this study point to the need for more support in the development of an integrative curriculum as well as continuous training for teachers. This article concludes that Aya Sophia Islamic School deserves to be a model for other educational institutions in Indonesia, with its ‘school-flavoured boarding school’ approach that is effective in shaping a smart and noble generation.